Defending Behavior and Victimization: Between- and Within-Person Associations - Malamut, Sarah T.; Garandeau, Claire F.; Salmivalli, Christina (Springer Science and Business Media LLC, 2025)
Anti-bullying interventions often encourage peer bystanders to defend their victimized peers. However, concerns have been raised that defending could put youth at risk for being victimized themselves. Despite these concerns, there is limited research on the longitudinal links between defending and victimization. Addressing limitations of previous research, the current study examined bidirectional associations between three types of peer-reported defending (comforting defending, assertive defending, reporting to authority) and (self- and peer-reported) victimization, teasing apart between- and within-person associations using random-intercept cross-lagged panel models. Participants included 5123 Finnish adolescents (45.9% self-identified as a boy; T1 Mage = 13.06, SD = 1.69, 93.5% born in Finland) in grades 4 to 9. There was a significant, negative between-person association only between comforting defending and self-reported victimization. There were no significant prospective within-person associations between any type of defending and self- or peer-reported victimization. The findings did not indicate that defending was a risk factor for subsequent victimization.